Diagnosis, Pathogenesis and Therapeutic Targets in Amyotrophic Lateral Sclerosis - Costa, Julia; Gomes, Catarina; de Carvalho, Mamede (CNS & Neurological Disorders - Drug Targets, 2010)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease of the motor system. The diagnosis is clinical, but additional investigations such as electromyography, transcranial magnetic stimulation and neuroimaging have demonstrated their usefulness in supporting diagnosis. Exhaustive research for the identification of molecular markers in the cerebrospinal fluid and plasma of ALS patients have been made; however, at present, there are no validated biomarkers for the disease. Between 5 to 10% of the ALS cases have a positive familial history, up to now eleven genes have been identified as associated with the disease. The most studied gene encodes for cupper, zinc superoxide dismutase enzyme. The identified abnormal genes potentially allow the generation of experimental cell and animal models to study the mechanisms of the disease and to test potential therapeutic compounds. The pathological characteristics of ALS include protein aggregation, proteasome inhibition, impaired axonal transport, mitochondria damage and apoptosis, oxidative stress, glutamate induced excitotoxicity, neuroinflammation and transcriptional dysfunction. Many compounds targeted to one or more of these mechanisms have been tested in multiple clinical trials. Nonetheless, nowadays only one drug, riluzole, has demonstrated a positive effect in the disease progression, but a number of recent compounds are promising in ALS therapy.
Keywords: lamotrigine